Pembingkaian Berita Pro Kontra Kader NasDem Terkait Anies Baswedan Sebagai Calon Presiden pada Medcom.id dan Detik.com - Lukman Hakim; Indah Suryawati (PROPAGANDA, 2023)
Â  The objective of this study is to discover and analyze the framing of medcom.id and detik.com regarding the pros and cons of NasDem cadres regarding Anies Baswedan as a presidential candidate. The research method is a qualitative approach, and the paradigm used in this study is constructivism. The objects of this study are the news texts of medcom.id and detik.com regarding the news on the pros and cons of NasDem cadres regarding Anies Baswedan as a presidential. Researchers discovered the framing carried by medcom.id and detik.com related to the news of the pros and cons of NasDem cadres regarding Anies Baswedan as a presidential candidate utilizing the framing analysis of Zhongdang Pan and Gerald M. Kosicki. In terms of framing devices (syntax, script, thematic, and rhetorical), it demonstrates that medcom.id in constructing social reality, particularly news related to the reaction of NasDem Party cadres following the announcement of Anies Baswedan as a presidential candidate prefers sources that support the declaration and appear biased. This is inextricably linked to the ideology and political policies of medcom.id, which has ties to NasDem Party Chairman Surya Paloh. The framing by detikcom also tends to support Anies' declaration as a presidential candidate. This could be seen from the sources chosen by detik.com supporting and defending the NasDem Party and Anies Baswedan after the announcement of the presidential candidate.